Development of Drive Cycle and Emission Concentration Models for In-Use Tricycles in Metro Manila. - Abuzo, Anabel A. (Philippine engineering journal.)
The objectives of the study are to develop the drive cycle for the tricycle, the local three-wheelers used for public transport in the Philippines, and quantify emissions from these vehicles as well as determine some of the factors that affect the emissions. The drive cycle for tricycle is developed with a maximum speed of 43.0 kph, maximum acceleration of 6.97 m/s2 (minimum acceleration of 6.44 m/s2), and average speed of 19.94 kph. Results indicate that 4-stroke tricycles have lesser HC and CO emission concentrations compared to the 2-stroke type. Regression analysis revealed that CO concentration is significantly affected by fuel-oil ratio and loading.